Divorce under the law reform (marriage and divorce) Act 1976 - An analysis of its rationals / Ishak Mohd Sharif - Mohd Sharif, Ishak (Faculty of Law, 1983)
“ The reform to the divorce law under the 1976 Act has not been that all innovative and revolutionary. There are some notable defects, some inevitable others uncalled for. Like a new consumer product in the marked only the package has changed, the ingredients still remain except perhaps with a few additions here and there - What was recognised as a fault principle has been branded as 'irretrievable breakdown'. What was meant to be a simple law suffers a complex disease of legal interpretation. Nevertheless, the Royal Commission should be commended in its effort to unify the law.” …..p. 32 “ Take adultery as an example. It has been recognised as a grave matrimonial misconduct that goes to the root of the marriage. It has been accepted as a cause of marriage breakdown. To disregard it would be contrary to public policy, to adopt it would be contrary to the policy of the new divorce law. It thereby becomes a question of priority. It is no easier than to resolve the problem of the ‘chicken and the egg’, the cause of breakdown or the effects of breakdown”….. p. 33